Solve using principles of zero products. (11v+9) (2v-6)=0 v= ___ (type an integerbor a simplified fraction, use a comma to separate as needed, type solution only once.

This is beautiful, because they already gave it to you in factored form.

All you have to do is say to yourself "This equation is a true statement

whenever the left side is zero, and the left side is zero when EITHER ONE

of the factors is zero. ". Then jump on it and beat it up. **First factor:**

11v + 9 = 0

11v = -9**v = -9/11****Second factor:**

2v - 6 = 0

2v = 6**v = 6/2 which is 3**.

\( (11v+9) (2v-6)=0 \\ \\ 11v+9=0 \ \ \ or \ \ \ 2v-6 =0 \\ \\ 11v= -9 \ \ \ or \ \ \ 2v=6 \\ \\ v= -\frac{9 }{11}\ \ \ or \ \ \ v=\frac{6}{2}\\ \\v= -\frac{9 }{11}\ \ \ or \ \ \ v=3 \)

RELATED: